2010
DOI: 10.1002/ejoc.201001048
|View full text |Cite
|
Sign up to set email alerts
|

Regiocontrolled Synthesis of Ring‐Fused Thieno[2,3‐c]pyrazoles through 1,3‐Dipolar Cycloaddition of Nitrile Imines with Sulfur‐Based Acetylenes

Abstract: 1,3‐Dipolar cycloadditions of C‐carboxymethyl‐N‐arylnitrile imines with substituted acetylenes bearing thiol or sulfone groups were studied. The sulfur controls the regiochemistry of the reaction, and this protocol was applied to the synthesis of ring‐fused thieno[2,3‐c]pyrazoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 33 publications
(29 reference statements)
0
18
0
1
Order By: Relevance
“…10 Moreover, the chemistry of fused pyrazole derivatives has received great attention due to their pharmacological importance. 11,12 It has been found that pyranopyrazoles are an important class of biologically active heterocycles. They are reported to possess a multiplicity of pharmacological properties including anticancer, 13 antimicrobial, 14 anti-inflammatory, 15 insecticidal and molluscicidal activities.…”
Section: Introductionmentioning
confidence: 99%
“…10 Moreover, the chemistry of fused pyrazole derivatives has received great attention due to their pharmacological importance. 11,12 It has been found that pyranopyrazoles are an important class of biologically active heterocycles. They are reported to possess a multiplicity of pharmacological properties including anticancer, 13 antimicrobial, 14 anti-inflammatory, 15 insecticidal and molluscicidal activities.…”
Section: Introductionmentioning
confidence: 99%
“…Так, у роботі [1] для одержання 1-арилзаміще-них естерів 4-формілпіразол-3-карбонових кис-лот із додатковою сульфідною функцією в поло-женні 5 була вдало використана циклоконденса-ція гідразиноїлхлоридів 1 із 3-сульфанілпропіна-лем 2 (схема 1).…”
Section: синтези пов'язані з формуванням пі-разольного циклуunclassified
“…221, 248, 265 ± 267, 273 ± 278 In the reaction between nitrile imines 169 and ethynylsulfonylbenzene 194 (R = H), catalytic amounts of Sc(OTf) 3 increase the yield of the 4-regioisomer 195. 221 The mechanism of its action is related to the formation of a transition state complex incorporating the methoxycarbonyl group of 1,3-dipole, the sulfonyl substituent of the dipolarophile and the catalyst. In the reaction of nitrile imines 169 with ethyl 3-(phenylsulfonyl)propiolate 194 (R = CO 2 Et), the addition of Lewis acids induces no change in the ratio of pyrazole regioisomers 195 and 196.…”
Section: Scheme 80mentioning
confidence: 99%
“…1,3-Dipolar cycloaddition of nitrile imines 169 to alkyne 194 without a catalyst or with the Sc(OTf)3 catalyst 221. …”
mentioning
confidence: 99%